Policy-makers and the R&D-patent relationship - Bruno van Pottelsberghe de la Potterie; Gaétan de Rassenfosse (Bruegel, 2008)
This policy contribution by Bruno von Pottelsberghe argues that the number of priority filings should be used as a patent-based measure of Europe's innovation performance. It also identifies several policies that may affect the R&D-patent relationship.
Keywords: 330; Patent; Messung; Forschungs- und Technologiepolitik; Wirkungsanalyse; EU-Staaten; Europa; Kanada; Singapur